Tingkat Harga Diri pada Pasien Diabetes Melitus - IGB ADI Sadnyana Putra; I Wayan Candra; I Gusti Ayu Harini; I Nengah Sumirta (Jurnal Gema Keperawatan, 2020)
The purpose of research to find the level of self- esteem of patients with Diabetes Mellitus at the Jembrana Polyclinic. This type of research design is descrivtive research design, with uses a purposive sampling technique. The result this research is majority of research subjects experienced low self-esteem. The conclusion this research is majority of research subjects experienced low self-esteem, as many as 13 people (59%), based on age is 36-55 years as13 people (59%), based on education a high school as14 people (63%), based on gender were men as13 people (59%), all subjects as POLRI members were 22 people (100%), based on long suffering from DM that was 6 months as 17 people (77%), research subjects who experienced obese as 8 people (36%).